A new proxy blind signature scheme. (2nd March 2012) - Fan, Kai; Wang, Yue; Li, Hui
There is no forward security in any proxy blind signature schemes today. The lack of forward security will impact the system security tremendously if the key is stolen. To avoid such a security problem this paper proposes a forward secure proxy blind signature scheme which employs the key evolution mechanism in a newly proposed proxy blind signature scheme. The security of proxy blind signature and the forward security are both analysed in the proposed scheme. Even if the current signature key is compromised, the attacker cannot forge signatures as if they had been generated before the key leakage. That is to say, signatures signed before the leakage are still valid.